RGO-CoO-Ni(OH)2 as an electrode material of supercapacitor - Chang, P.Y.; Majid, S.R. (2015)
A composite film containing reduced graphene oxide (RGO), CoO and Ni(OHJ2 has been prepared from CO(N03)2.6H20 and 1 Ji(N03h6H20 with its Co:Ni ratio of 2:1 using simple electrodeposition technique. The effect of scan rate on the electrode film is highlighted. Changes in cyclic voltammetry (CV) curves and thus morphologies of the electrode film after CV test are identified. The electrode film exhibits specific capacitance of 558 F g-l at 5 mV sI in 1M KOH. However, the cycling Stability of the electrode film over 1000 cycles is low and need to be improved further. The morphology of the electrode film is demonstrated using field emission scanning electron rmcrosope (FESEM).